2017
DOI: 10.11114/jets.v5i7.2317
|View full text |Cite
|
Sign up to set email alerts
|

Compare the Values of Blood Lactate and Heart Rate of Kickboxers during Kickboxing Matches

Abstract: The aim of this study was to compare the values of heart rate (HR) and blood lactate (BL) of kickboxers during kickboxing match.This study was conducted with the participation of 18 male and 16 female sportsman in Turkish Kickboxing championship, an organization of Turkish Kickboxing Federation. After the participant athletes read and signed informed voluntary consent form (BGOF) prepared for them, the measurements were collected. While no significant difference was found between ages, pre-match HR, post-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The significant changes in ABB parameters and blood oxygen and carbon dioxide saturation immediately after the bout indicate a large contribution of anaerobic metabolism in generating the physical work and gas exchange rate in kickboxers. The examinations conducted by other authors in kickboxers immediately after each of three rounds or after an entire bout showed a significant decline in muscle strength, and a progressive increase in blood lactate levels and heart rates [ 43 , 44 , 45 , 48 ]. In our study there were very weak correlations between activity in attacks and rise of hydrogen ion levels, but a significant positive link between activity and post bout increase of total CO 2 level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant changes in ABB parameters and blood oxygen and carbon dioxide saturation immediately after the bout indicate a large contribution of anaerobic metabolism in generating the physical work and gas exchange rate in kickboxers. The examinations conducted by other authors in kickboxers immediately after each of three rounds or after an entire bout showed a significant decline in muscle strength, and a progressive increase in blood lactate levels and heart rates [ 43 , 44 , 45 , 48 ]. In our study there were very weak correlations between activity in attacks and rise of hydrogen ion levels, but a significant positive link between activity and post bout increase of total CO 2 level.…”
Section: Discussionmentioning
confidence: 99%
“…Ass mentioned earlier, boxing, kickboxing and taekwondo athletes are exposed to head injuries during competitions, which can reduce cognitive and executive abilities and impair technical skills [ 41 , 42 ]. In addition, three repeated maximal physical efforts may contribute to physiological changes [ 43 , 44 ], which are, in part, responsible for accumulation of fatigue. The most visible symptom of increasing fatigue during successive bouts may be an increasing number of pauses and total time of pauses [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Teniendo en cuenta esto, se debe considerar el deporte y/o las características de cada individuo para así determinar cuándo se debe entrenar la capacidad anaeróbica o la capacidad aeróbica, como lo refiere Karadağ (2017) an organization of Turkish Kickboxing Federation. After the participant athletes read and signed informed voluntary consent form (BGOF quien indica que hay deportes como el kickboxing el cual maneja diferentes intensidades, por lo tanto, emplean tanto la capacidad aeróbica y la anaeróbica las cuales deben ser evaluadas por el entrenador de kickboxer y a partir de sus resultados podrá determinar las cargas y los ejercicios para sus entrenamientos.…”
Section: Sistema Anaeróbicounclassified
“…A number of studies have been carried out in order to examine the effects of these metabolic events on the performance of athletes. Especially the effects of different study programs during acute or chronic period on biochemical parameters have become the focus of many researchers (Bond et al, 1991;Karadağ, 2017). These scientific studies provide us with highly important information that is specific to the performed sport.…”
Section: Introductionmentioning
confidence: 99%